Using Cooperative Script to Enhance Students' Comprehension of Narrative Text - Arief Rahman; Rojab Siti Rodliyah (Jurnal Penelitian Pendidikan, 2022)
This study aims to determine the efficacy of implementing cooperative scripts to improve students’ reading comprehension of narrative texts in the first grade at SMAN 8 South Tangerang during the 2020/21 academic year. This study includes 39 students from X Science 1 and 39 from X Science 2 as samples. The English test results of the students measure the success of this study. Based on the stated purpose, the researcher designed a quasi-experimental study. After taking the English Test, the student acquired reading comprehension skills. The examination was based on the tenth-grade English textbook. Through pre-test and post-test, the researcher obtained the results. The researcher in the data analysis procedure utilized normality, homogeneity, and a T-test. The examination of the data revealed a substantial difference between the reading comprehension achievement of students in experimental classes, which were taught using the Cooperative Script technique, and students in control classes, who were not. It might be seen by comparing the pre-test and post-test results of students. The experimental class had a mean pre-test score of 59.69 and a post-test score of 73.94. In contrast, the mean score on the pretest for the control group was 58.87, while the mean score on the posttest was 70.41.